Randomized Clinical Trial of High-Dose Rifampicin With or Without Levofloxacin Versus Standard of Care for Pediatric Tuberculous Meningitis: The TBM-KIDS Trial . (15th March 2022) - Paradkar, Mandar S; Devaleenal D, Bella; Mvalo, Tisungane; Arenivas, Ana; Thakur, Kiran T; Wolf, Lisa; Nimkar, Smita; Inamdar, Sadaf; Giridharan, Prathiksha; Selladurai, Elilarasi; Kinikar, Aarti; Valvi, Chhaya; et al.
Abstract: Background: Pediatric tuberculous meningitis (TBM) commonly causes death or disability. In adults, high-dose rifampicin may reduce mortality. The role of fluoroquinolones remains unclear. There have been no antimicrobial treatment trials for pediatric TBM. Methods: TBM-KIDS was a phase 2 open-label randomized trial among children with TBM in India and Malawi. Participants received isoniazid and pyrazinamide plus: ( i ) high-dose rifampicin (30 mg/kg) and ethambutol (R30 HZE, arm 1); ( ii ) high-dose rifampicin and levofloxacin (R30 HZL, arm 2); or ( iii ) standard-dose rifampicin and ethambutol (R15 HZE, arm 3) for 8 weeks, followed by 10 months of standard treatment. Functional and neurocognitive outcomes were measured longitudinally using Modified Rankin Scale (MRS) and Mullen Scales of Early Learning (MSEL). Results: Of 2487 children prescreened, 79 were screened and 37 enrolled. Median age was 72 months; 49%, 43%, and 8% had stage I, II, and III disease, respectively. Grade 3 or higher adverse events occurred in 58%, 55%, and 36% of children in arms 1, 2, and 3, with 1 death (arm 1) and 6 early treatment discontinuations (4 in arm 1, 1 each in arms 2 and 3). By week 8, all children recovered to MRS score of 0 or 1. Average MSEL scores were significantly better in arm 1 than arm 3 in fine motor, receptive language, and expressive language domains ( P < .01). Conclusions: In a pediatric TBM trial, functional outcomes were excellent overall. The trend toward higher frequency of adverse events but better neurocognitive outcomes in children receiving high-dose rifampicin requires confirmation in a larger trial. Clinical Trials Registration: NCT02958709. Abstract : In this first-ever antibiotic treatment trial for pediatric tuberculous meningitis, children receiving high-dose rifampicin (with or without levofloxacin) had similar functional outcomes and a trend toward better neurocognitive outcomes than those receiving a standard-dose rifampicin-containing regimen.